Regulation of 3-hydroxy-3-methylglutaryl-coenzyme A reductase activity in murine epidermis. Modulation of enzyme content and activation state by barrier requirements. - Proksch, E (1990)
Epidermal cholesterol biosynthesis is regulated by barrier function. We quantitated the amount and activation state (phosphorylation-dephosphorylation) of the rate-limiting enzyme, 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase, in epidermis before and after barrier disruption. In murine epidermis we found high enzyme activity (1.75 +/- 0.02 nmol/min per mg protein). After acute barrier disruption, enzyme activity began to increase after 1.5 h, reaching a maximum increase by 2.5 h, and returned to normal by 15 h. Chronic barrier disruption increased total enzyme activity by 83%. In normal epidermis, measurement of HMG CoA reductase activity in microsomes isolated in NaF- vs. NaCl-containing buffers demonstrated that 46 +/- 2% of the enzyme was in the active form. After acute or chronic barrier disruption, a marked increase in the percentage of HMG CoA reductase in the active form was observed. Acute disruption increased enzyme activation state as early as 15 min, reaching a maximum after 2.5 h, with an increase still present at 15 h, indicating that changes in activation state had a close temporal relationship with barrier function. Increases in total HMG CoA reductase activity occurred only after profound barrier disruption, whereas changes in activation state occur with lesser degrees of barrier disruption. Artificial correction of barrier function prevented the increase in total HMG CoA reductase activity, and partially prevented the increase in enzyme activation. These results show that barrier requirements regulate epidermal cholesterol synthesis by modulating both the HMG CoA reductase amount and activation state.